Phase II basket trial of Dual Anti-CTLA-4 and Anti-PD-1 blockade in Rare Tumors (DART) SWOG S1609: adrenocortical carcinoma cohort - Howard Streicher; Elad Sharon; Razelle Kurzrock; Young Kwang Chae; Benjamin Tan; Megan Othus; Christine McLeod; Charles Blanke; Helen X Chen; Sandip P Patel; Gabby Lopez; Tridu Huynh; et al. (Journal for ImmunoTherapy of Cancer)
Objectives Multiple common cancers benefit from immunotherapy; however, less is known about efficacy in rare tumors. We report the results of the adrenocortical carcinoma cohort of NCI/SWOG S1609 Dual Anti-CTLA-4 and Anti-PD-1 blockade in Rare Tumors.Design/setting A prospective, phase 2 clinical trial of ipilimumab plus nivolumab was conducted by the SWOG Early Therapeutics and Rare Cancers Committee for multiple rare tumor cohorts across >1,000 National Clinical Trial Network sites.Participants 21 eligible patients were registered. Median age was 53 years (range 26–69); 16 (76%) were women.Interventions Ipilimumab 1 mg/kg intravenously every 6 weeks with nivolumab 240 mg intravenously every 2 weeks was administered until disease progression, symptomatic deterioration, treatment delay for any reason >56 days, unacceptable or immune-related toxicity with inability to decrease prednisone to <10 mg daily, or per patient request.Main outcome measures The primary endpoint was the overall response rate (ORR) (RECIST V.1.1). Secondary endpoints include clinical benefit rate (CBR) (includes stable disease (SD)>6 months), progression-free survival (PFS), overall survival (OS), and toxicity. Immune-related outcomes included immune ORR (iORR), immune CBR (iCBR), and immune PFS (iPFS). A two-stage design was used assuming: null=5% alternative=30%, n=6 in the first stage, 16 max, one-sided alpha=13%.Results The median number of prior therapy lines was 2 (range: 1–9). 3 of 21 patients attained confirmed partial response (PR) (ORR=14%). In addition, one patient had an unconfirmed PR; one, stable disease (SD)>6 months; one, immune-related RECIST (iRECIST) PR (iPR); and one patient attained iSD>6 months: clinical benefit rate (response or SD>6 months)=5/21 (24%), iORR=4/21 (19%), iCBR=7/21 (33%). The 6-month PFS was 24%; 6-month iPFS, 33%. The PFS for patients (N=7) with iRECIST clinical benefit were 57, 52, 18, 15, 13, 7, and 7 months. The 6-month OS was 76%; the median OS, was 15.8 months. The most common toxicities were fatigue (62%) and rash (38%), and the most common grade 3/4 immune-related adverse events were hepatic dysfunction (9.5%) and adrenal insufficiency (9.5%). Treatment-related adverse events leading to discontinuation of therapy in four patients (21%). There were no grade 5 adverse events.Conclusions Ipilimumab plus nivolumab is active in refractory metastatic adrenocortical cancer meeting the primary endpoint of the study, with a 19% iORR and 33% iCBR (includes SD/iSD>6 months) and with the longest PFS/iPFS of 52 and 57 months.Trial registration number NCT02834013 (registered 15 July, 2016; https://clinicaltrials.gov/ct2/show/NCT02834013).